2015
DOI: 10.2174/1570159x13999150318113642
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Vocalizations as a Measure of Affect in Preclinical Models of Drug Abuse: A Review of Current Findings

Abstract: The present review describes ways in which ultrasonic vocalizations (USVs) have been used in studies of substance abuse. Accordingly, studies are reviewed which demonstrate roles for affective processing in response to the presentation of drug-related cues, experimenter- and self-administered drug, drug withdrawal, and during tests of relapse/reinstatement. The review focuses on data collected from studies using cocaine and amphetamine, where a large body of evidence has been collected. Data suggest that USVs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 143 publications
(224 reference statements)
1
41
0
Order By: Relevance
“…We observed that suvorexant attenuated 50-kHz USVs during each of pre- and post-lever time-points. Our prior work shows that suvorexant pretreatment suppresses cocaine-evoked elevations in ventral striatal dopamine (Gentile et al 2017) which supports the hypothesis that mesolimbic dopamine underlies the elicitation of 50-kHz USVs (for reviews, see Barker et al 2015; Brudzynski 2015). From the three categories of call types analyzed in the present report, 50-kHz USV call type remained stable irrespective of suvorexant pre-treatment with majority of calls belonging to FM 1–2 call type which supports earlier work describing USVs associated with cocaine-paired cue presentation (Meyer et al 2012).…”
Section: Discussionsupporting
confidence: 78%
“…We observed that suvorexant attenuated 50-kHz USVs during each of pre- and post-lever time-points. Our prior work shows that suvorexant pretreatment suppresses cocaine-evoked elevations in ventral striatal dopamine (Gentile et al 2017) which supports the hypothesis that mesolimbic dopamine underlies the elicitation of 50-kHz USVs (for reviews, see Barker et al 2015; Brudzynski 2015). From the three categories of call types analyzed in the present report, 50-kHz USV call type remained stable irrespective of suvorexant pre-treatment with majority of calls belonging to FM 1–2 call type which supports earlier work describing USVs associated with cocaine-paired cue presentation (Meyer et al 2012).…”
Section: Discussionsupporting
confidence: 78%
“…Positive and negative affective states can be non-invasively probed in rats by recordings ultrasonic vocalizations (USVs); rewarding stimuli evoke 50-kHz USVs whereas aversive stimuli evoke 22-kHz USVs (e.g., Blanchard et al , 1991; Sanchez, 1993; Brudzynski and Pniak, 2002). In models of substance use disorders, 50-kHz USVs consistently associate with systemic- and self-administration of cocaine and amphetamine whereas 22-kHz USVs associate with corresponding drug withdrawal states (e.g., Barros and Miczek, 1996; Wintink and Brudzynski, 2001; Barker et al , 2010; for review, see Barker et al , 2015). Production of positive 50-kHz USVs are supported by mesolimbic dopamine (DA) transmission, as direct infusion of amphetamine into the nucleus accumbens (NAcc), a principal target structure of DA-producing neuronal afferents from ventral tegmental area (VTA), readily evokes 50-kHz USVs (Burgdorf et al , 2001; Thompson et al , 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our data obtained with the CPP (a classical and well established paradigm to study the rewarding properties of drug and non-drug stimuli; see Tzschentke 2007 for a review), showed that rats, during the test day, kept approaching the compartment associated with the USV in absence of their playback. Considering the 50-kHz USV are uttered during – mostly positive – various social interactions (Burgdorf et al 2008), but also after exposure to food and drugs (Browning et al 2011; Barker, Simmons, & West 2015), or in mildly aversive situations as a short social isolation (Wöhr et al 2007), we can reasonably suppose that the social and rewarding aspects of the 50-kHz USV could overlap in some circumstances, while in other situations one aspect could prevail on the other. Further research is necessary to investigate this point.…”
Section: Discussionmentioning
confidence: 99%
“…This acoustic communication could thus play an important role in the effects mediated by the peer presence on drug and food intake. Although recording USV of rats self-administering drugs and palatable food as sucrose is common to assess the emotional status of the animals (Browning et al 2011; Barker, Simmons, & West 2015), no study has ever evaluated the effects of USV playback on drug and food intake, albeit other recent studies have shown that USV playback in rats is an essential tool to investigate different human brain disorders, especially those involving social communication deficits (Wöhr & Schwarting 2017). Moreover there are no studies regarding the neurobiological basis of the proximal social factor’s effects on drug and food consumption.…”
Section: Introductionmentioning
confidence: 99%